Transformative imaging of the extracranial facial nerve by MRI and Microsoft HoloLens2. Issue 1 (January 2022) - Saadya, Ahmad; Chegini, Soudeh; Bray, Timothy; Morley, Simon; Beale, Timothy; McGurk, Mark
Abstract : Introduction : The facial nerve is a small structure that can be displaced into unexpected positions by tumors growing within the parotid gland. Hololens2 is an augmented reality headset which allows the holographic projection of images onto the wearers view of their surroundings creating a mixed image. In this study we assessed the ability of 3T MRI and Hololens2 to visualise the path of facial nerve around parotid tumors and the impact on surgical planning. Methods : 18 patients with parotid neoplasms underwent 3T MRI imaging. MRI images were subsequently segmented using 3D slicer software and uploaded into a mixed reality device (Microsoft HoloLens2) using ApoQlar software. This created a 3D hologram of the facial nerve and the relations to the surrounding structure.Images were later compared to observations made intraoperatively. Results : 18 patients with parotid neoplasms were included in this study. 14 females and 4 males between the ages of 18 and 66. This included 13 benign and 5 malignant neoplasms. Identical match of projected 3D hologram images to the surgical findings was present in 100% of the patients. Age, sex, tumor type, size, site did not make a change in the predicted images. Conclusions : The facial nerve can be faithfully visually traced in 3D hologram as it passes through the parotid gland and weaves its way past resident tumors. This allows surgeons to be forewarned of unusual configuration of the facial nerve and also opens up the opportunity to plan and execute operations in a way that minimizes nerve contact.